'I think I'm agnostic because I have a Muslim father and a Catholic mother'. Religious transmission to children from interfaith unions in Barcelona. Issue 1 (2nd January 2023) - Rodríguez-Reche, Cristina; Solana-Solana, Miguel; Rodríguez-García, Dan
ABSTRACT: Based on an ethnographic study conducted with in-depth interviews, this study shows how the children of interfaith couples whose members were socialised in the Catholic and/or Muslim faiths, respectively, internalise the religious and/or cultural values that their parents transmit to them. We furthermore point out that the negotiation processes of both transmission by the couple and inheritance by the descendants are often conditioned by social and contextual factors, including the gradual process of religious secularisation. We shall analyse the consequences that this factor, increasingly common in Barcelona, has on these interfaith negotiation, transmission and inheritance processes.